Integrating Local Wisdom in Tourism Strategies to Enhance Community Economic Growth - Amtiran, Paulina Y.; Aryo, Muhammad D.; Tkela, Melianu E.; Loinenok, Juniarto J.; Pong, Nekkidin S. A. (Dinasti Publisher, 2026)
This study examines the effectiveness of a local wisdom-based tourism development approach as a strategy to enhance community income growth while ensuring cultural and environmental sustainability. The research employs a descriptive qualitative method, utilizing findings from Focus Group Discussions (FGDs) and a case study conducted in Southwest Sumba Regency. The research concludes that the key to success lies in synergistic collaboration among the community, local government, and the private sector, with a focus on local community sovereignty. Tourism will achieve maximum effectiveness when communities and traditional institutions are elevated from passive objects to active agents controlling tourism potential. This can be realized through: (1) Increasing equitable economic welfare, measured by the growth in turnover of small businesses (such as homestays and crafts) and job creation; (2) Preserving culture and traditional values, where traditional rules serve as operational standards and tools for socio-cultural governance; and (3) Synergistic and transparent governance, supported by strengthening the capacity of Pokdarwis and BUMDes. The primary implication of this research is that recognizing communities as the principal custodians of cultural and natural resources transforms tourism from a mere revenue generator into an effective tool for preserving traditions, supported by direct community incentives and responsibilities. The sustainability of this model relies heavily on the proactive role of local governments as facilitators and the engagement of a responsible private sector committed to local empowerment.